Breaking our silence gloucester men speak out against domestic abuse - Steiner, Susan; Greenbaum, William; Ferrini, Henri; GMADA (Gloucester, MA : Gloucester Men Against Domestic Abuse, 2002)
This documentary gives insight into the activist efforts of a group of men in the town of Gloucester, MA. Includes footage from anti-violence marches, and centers on community men speaking out against violence and domestic abuse
Camera, Henry Ferrini ; music Ani DiFranco, Andy Stochansky
Street interviews: Kyle Butler Harris
Keywords: Family violence; Abusive men